Carbon nanotube dispersion
The CNT dispersion with specific characteristics of CNT bundles and dispersant molecular weight improves the stability and conductivity of molded bodies, addressing the limitations of conventional CNT dispersions.
Patent Information
- Application Number
- JP2023203426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-06-11
AI Technical Summary
Conventional carbon nanotube (CNT) dispersions face challenges in enhancing the conductivity and stability of molded bodies formed from them.
A CNT dispersion containing single-walled CNTs, a solvent, and a dispersant with a weight average molecular weight of less than 40,000, where the average length of CNT bundles is 1.50 μm or more, the average diameter is less than 14.7 nm, and the number of bundles with a diameter exceeding 30.0 nm is 10 or less, is used to achieve improved stability and conductivity.
The CNT dispersion exhibits excellent temporal stability and enhances the conductivity of molded bodies, such as carbon films and electrodes, by ensuring sufficient length and uniform diameter of CNT bundles.
Smart Images

Figure 2025088617000001 
Figure 2025088617000002 
Figure 2025088617000003
Abstract
Description
Technical Field
[0001] The present invention relates to a carbon nanotube dispersion.
Background Art
[0002] Conventionally, carbon nanotubes (hereinafter sometimes abbreviated as "CNT") have attracted attention as materials excellent in properties such as conductivity, heat conductivity, and strength.
[0003] Here, although the properties of each individual CNT are excellent, since the outer diameter is small, CNTs are easily bundled (prone to bundling) by van der Waals forces. Therefore, conventionally, CNTs have been once dispersed in a solvent to prepare a carbon nanotube dispersion (CNT dispersion). The obtained CNT dispersion is used, for example, in the production of a molded body such as a carbon film formed by aggregation of a plurality of CNTs and an electrode for a secondary battery.
[0004] Therefore, in recent years, attempts have been made to improve various properties of the molded body by improving the CNT dispersion. For example, Patent Document 1 discloses a CNT dispersion containing CNTs, a solvent, and a dispersant, wherein the average outer diameter of the CNTs, the half-value width of the peak at a diffraction angle 2θ = 25° ± 2°, and the G / D ratio are each within a predetermined range. According to Patent Document 1, by using the CNT dispersion, a resin composition, an electrode film, etc. excellent in conductivity can be obtained. Further, Patent Document 2 discloses a CNT dispersion containing CNTs, a dispersant, and a solvent, wherein the average outer diameter, BET specific surface area, and average fiber length of the CNTs are each within a predetermined range. According to Patent Document 2, by using the CNT dispersion, a resin composition, an electrode film, etc. excellent in conductivity and adhesion can be obtained.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
[0006] However, in recent years, further improvement in various properties of a molded body formed from a CNT dispersion has been demanded. However, the above-mentioned conventional CNT dispersion has room for improvement in terms of further enhancing the conductivity of the molded body. In addition, the above-mentioned conventional CNT dispersion has room for further improvement in the stability over time of the dispersion state.
[0007] Therefore, an object of the present invention is to provide a carbon nanotube dispersion that is excellent in the stability over time of the dispersion state and can form a molded body excellent in conductivity. [Means for Solving the Problems]
[0008] The present inventor has intensively studied for the purpose of solving the above problems. Here, the present inventor focused on a bundle (hereinafter, may be referred to as a "CNT bundle") formed by aggregation of a plurality of CNTs in a CNT dispersion. Then, the present inventor found that in a CNT dispersion containing a plurality of CNTs containing single-walled CNTs, a solvent, and a dispersant having a weight average molecular weight of less than a predetermined value, if the average length of the CNT bundle is set to a predetermined value or more, the average diameter of the CNT bundle is set to less than a predetermined value, and the ratio of CNT bundles having a diameter exceeding 30.0 nm is set to a predetermined value or less, a CNT dispersion excellent in the stability over time of the dispersion state and capable of enhancing the conductivity of the molded body can be obtained, and completed the present invention.
[0009] That is, this invention aims to advantageously solve the above problems, and according to the present invention, the CNT dispersions of the following [1] to [5] are provided.
[0010] 〔1〕A carbon nanotube dispersion liquid containing a plurality of carbon nanotubes, a solvent, and a dispersant having a weight average molecular weight of less than 40,000, wherein the plurality of carbon nanotubes include single-walled carbon nanotubes, at least a part of the plurality of carbon nanotubes forms a carbon nanotube bundle, the average length of the carbon nanotube bundle is 1.50 μm or more, the average diameter of the carbon nanotube bundle is less than 14.7 nm, and among 100 carbon nanotube bundles, the number of those with a diameter exceeding 30.0 nm is 10 or less. A CNT dispersion liquid containing a plurality of CNTs containing single-walled CNTs, a solvent, and a dispersant having a weight average molecular weight less than the above value, wherein the average length of the CNT bundle is the above value or more, the average diameter of the CNT bundle is less than the above value, and among 100 CNT bundles, the number of those with a diameter exceeding 30.0 nm is the above value or less has excellent temporal stability of the dispersed state and can exhibit excellent conductivity in a molded body. In the present invention, the "average length of the carbon nanotube bundle", the "average diameter of the carbon nanotube bundle", and the "number of those with a diameter exceeding 30.0 nm among 100 carbon nanotube bundles" can be measured using the methods described in the examples of this specification, respectively. In the present invention, the "weight average molecular weight" of the dispersant can be measured as a standard polystyrene conversion value using gel permeation chromatography, and specifically, it can be measured using the method described in the examples of this specification.
[0011] 〔2〕The carbon nanotube dispersion liquid according to the above 〔1〕, wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less. If the G / D ratio of the CNTs is within the above range, the temporal stability of the dispersed state of the CNT dispersion liquid can be further improved, and the conductivity of the molded body can be further enhanced. In the present invention, the "G / D ratio" refers to the ratio of the G-band peak intensity to the D-band peak intensity in the Raman spectrum, and it can be measured using the method described in the examples of this specification.
[0012] 〔3〕The carbon nanotube dispersion according to the above [1] or [2], wherein the average aspect ratio of the carbon nanotube bundle is 110 or more. If the average aspect ratio of the CNT bundle is equal to or greater than the above value, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced. In the present invention, the "average aspect ratio" of the CNT bundle can be obtained by calculating the ratio of the average length to the average diameter (average length / average diameter) of the CNT bundle.
[0013] 〔4〕The carbon nanotube dispersion according to any one of the above [1] to [3], wherein the dispersant is carboxymethyl cellulose or a salt thereof. By using carboxymethyl cellulose or a salt thereof as the dispersant, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0014] 〔5〕The carbon nanotube dispersion according to the above [4], wherein the degree of etherification of the carboxymethyl cellulose is 0.5 or more and 0.9 or less. If the degree of etherification of the carboxymethyl cellulose used as the dispersant is within the above range, aggregation of CNTs in the CNT dispersion can be suppressed, and the temporal stability of the dispersion state of the CNT dispersion can be further improved. In the present invention, the "degree of etherification" of carboxymethyl cellulose refers to the average value of the number of hydroxyl groups substituted by a substituent (carboxymethyl group) per unit of anhydroglucose constituting carboxymethyl cellulose, and can take a value greater than 0 and less than 3. The larger the degree of etherification, the smaller the proportion of hydroxyl groups in one molecule of carboxymethyl cellulose (i.e., the larger the proportion of substituents), and the smaller the degree of etherification, the larger the proportion of hydroxyl groups in one molecule of carboxymethyl cellulose (i.e., the smaller the proportion of substituents). This degree of etherification (degree of substitution) can be determined by the method described in JP-A-2011-34962.
Advantages of the Invention
[0015] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid that is excellent in the temporal stability of the dispersed state and can form a molded body excellent in conductivity.
Embodiments for Carrying Out the Invention
[0016] Hereinafter, embodiments of the present invention will be described in detail. Here, the CNT dispersion liquid of the present invention is not particularly limited, and for example, it can be used as a material for forming a molded body such as a carbon film or an elastomer molded body, an electrode for a secondary battery, and the like.
[0017] (Carbon Nanotube Dispersion Liquid) The CNT dispersion liquid of the present invention contains at least CNT, a solvent, and a dispersant, and optionally further contains components other than CNT, the solvent, and the dispersant (other components). Note that at least a part of a plurality of CNTs is a single-walled CNT, and CNT bundles are formed in the CNT dispersion liquid. Here, the CNT dispersion liquid of the present invention contains a dispersant having a weight average molecular weight of less than 40,000, the average length of the CNT bundles is 1.50 μm or more, the average diameter of the CNT bundles is less than 14.7 nm, and the number of CNT bundles having a diameter exceeding 30.0 nm among 100 CNT bundles is 10 or less. Note that the CNT bundle is formed by a plurality of CNTs aggregating in a bundle shape (a bundled state) along the long axis direction of the CNT.
[0018] Moreover, the CNT dispersion of the present invention contains a dispersant having a weight average molecular weight of less than a predetermined value, the average length of the CNT bundles is equal to or greater than a predetermined value, the average diameter of the CNT bundles is less than a predetermined value, and the number of CNT bundles among 100 CNT bundles having a diameter exceeding 30.0 nm is equal to or less than a predetermined value. Therefore, the CNT dispersion has excellent temporal stability in the dispersed state and can exhibit excellent conductivity in the molded body. Although the reason for obtaining the above effects by using the CNT dispersion of the present invention is not clear, it is presumed as follows.
[0019] The inventor of the present invention focused on CNT bundles composed of a plurality of CNTs in the CNT dispersion in order to improve the dispersibility of the CNT dispersion. As the average diameter of the CNT bundles decreases, the number of CNTs constituting each bundle decreases. Further, as the number of CNT bundles among 100 CNT bundles having a diameter exceeding 30.0 nm decreases, the number of CNT bundles present in the CNT dispersion increases. In the CNT dispersion of the present invention, the average diameter of the CNT bundles is less than 14.7 nm, and the number of CNT bundles among 100 CNT bundles having a diameter exceeding 30.0 nm is 10 or less, so that the number of CNT bundles present in the CNT dispersion is sufficiently ensured. In addition, in the dispersion of the present invention, since the average length of the CNT bundles is 1.50 μm or more, the length of the CNT bundles present in the CNT dispersion is sufficiently ensured. In addition, the CNT dispersion of the present invention contains a dispersant having a weight average molecular weight of less than 40,000. In the CNT mixture before the dispersion treatment, CNTs are likely to form bundle-like aggregates (CNT aggregates) due to van der Waals forces. However, a dispersant having a small weight average molecular weight penetrates into the gaps between the CNT aggregates and can function well as a dispersant. Thus, due to the sufficient number and length of the CNT bundles and the penetration effect of the dispersant into the CNT aggregates, in the CNT dispersion of the present invention, CNTs can be stably dispersed over time (the temporal stability of the dispersed state can be improved). Further, by using such a CNT dispersion, a good conductive path can be formed by distributing CNT bundles having a sufficient length in the molded body. For the above reasons, the CNT dispersion of the present invention is excellent in the temporal stability of the dispersed state, and it is considered that if the CNT dispersion is used, the molded body can exhibit excellent conductivity.
[0020] <cnt> The CNT is not particularly limited as long as it contains single-walled CNTs. As the CNT, only single-walled CNTs may be used, or single-walled CNTs and multi-walled CNTs may be used in combination.
[0021] [[Properties]] [Average length of CNT bundles] The average length of the CNT bundles needs to be 1.50 μm or more, preferably 1.55 μm or more, more preferably 1.60 μm or more, still more preferably 1.65 μm or more, even more preferably 1.70 μm or more, and particularly preferably 1.75 μm or more. When the average length of the CNT bundles is less than 1.50 μm, the conductivity of the molded body decreases. Further, the upper limit of the average length of the CNT bundles is not particularly limited, and for example, it can be 3.50 μm or less, 3.00 μm or less, or 2.50 μm or less. Incidentally, the average length of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the length of the raw material CNT (the CNT used as a raw material when preparing the CNT dispersion), the type and amount of the dispersant, and the conditions of the dispersion treatment. For example, when a wet jet mill is used for the dispersion treatment, the average length of the CNT bundles becomes smaller by increasing the pressure applied to the mixed liquid passing through the wet jet mill, and becomes larger by decreasing the pressure. Also, by increasing the number of passes (the number of times the total amount of the mixed liquid passes through the wet jet mill) of the dispersion treatment by the wet jet mill, the average length of the CNT bundles in the CNT dispersion becomes smaller, and by decreasing the number of passes, the average length becomes larger.
[0022] [Average diameter of CNT bundles] The average diameter of the CNT bundles should be less than 14.7 nm, preferably 14.6 nm or less. When the average diameter of the CNT bundles is 14.7 nm or more, the temporal stability of the dispersion state of the CNT dispersion decreases, and the conductivity of the resulting molded body also decreases. Also, the lower limit of the average diameter of the CNT bundles is not particularly limited, and for example, it can be 12.0 nm or more, 12.5 nm or more, or 13.0 nm or more. Incidentally, the average diameter of the CNT bundles in the CNT dispersion can be adjusted, for example, by changing the diameter of the raw material CNT, the type and amount of the dispersant, and the conditions of the dispersion treatment. For example, when a wet jet mill is used for the dispersion treatment, the average diameter of the CNT bundles decreases by increasing the pressure applied to the mixed liquid passing through the wet jet mill, and increases by decreasing the pressure. Also, the average diameter of the CNT bundles in the CNT dispersion decreases by increasing the number of passes of the dispersion treatment using the wet jet mill, and increases by decreasing the number of passes.
[0023] [Number of CNT bundles with a diameter exceeding 30.0 nm] Out of 100 CNT bundles, the number of CNT bundles with a diameter exceeding 30.0 nm should be 10 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less. When the number of CNT bundles with a diameter exceeding 30.0 nm is more than 10, the temporal stability of the dispersion state of the CNT dispersion decreases, and the conductivity of the resulting molded body also decreases. Also, the lower limit of the number of CNT bundles with a diameter exceeding 30.0 nm out of 100 CNT bundles is not particularly limited, and for example, it can be 0 or more, or 1 or more. Note that the CNT dispersion of the present invention may not contain CNT bundles with a diameter exceeding 30.0 nm, and the number of CNT bundles with a diameter exceeding 30.0 nm out of 100 CNT bundles may be 0. And the number of CNT bundles with a diameter exceeding 30.0 nm can be adjusted, for example, by changing the length and diameter of the raw CNTs, the type and amount of the dispersant, and the conditions of the dispersion treatment. For example, when a wet jet mill is used for the dispersion treatment, increasing the pressure applied to the mixed liquid passing through the wet jet mill decreases the number of CNT bundles with a diameter exceeding 30.0 nm, and decreasing the pressure increases the number. Also, increasing the number of passes of the dispersion treatment by the wet jet mill decreases the number of CNT bundles with a diameter exceeding 30.0 nm, and decreasing the number of passes increases the number.
[0024] [Average aspect ratio of CNT bundles] The average aspect ratio of the CNT bundles is preferably 103 or more, more preferably 110 or more, still more preferably 115 or more, even more preferably 120 or more, and particularly preferably 125 or more. If the average aspect ratio of the CNT bundles is 103 or more, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced. The upper limit of the average aspect ratio of the CNT bundles is not particularly limited and can be, for example, 220 or less, 200 or less, or 180 or less.
[0025] [G / D ratio] The G / D ratio of the CNTs is preferably 0.5 or more, more preferably 1 or more, preferably 120 or less, more preferably 90 or less, still more preferably 60 or less, even more preferably 30 or less, and particularly preferably 10 or less. If the G / D ratio of the CNTs is within the above range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0026] [Content ratio] The content ratio of CNTs in the CNT dispersion is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less, with the total amount of the CNT dispersion being 100% by mass. If the content ratio of CNTs in the CNT dispersion is 0.01% by mass or more, the conductivity of the molded body can be further enhanced, and the productivity of the molded body can be improved. On the other hand, if the content ratio of CNTs in the CNT dispersion is 2% by mass or less, the temporal stability of the dispersion state of the CNT dispersion can be further improved.
[0027] <Solvent> The CNT dispersion of the present invention may contain only water as the solvent, may contain only an organic solvent (e.g., esters, ketones, alcohols) as the solvent, or the solvent may be a mixture of water and an organic solvent. From the viewpoint of further improving the temporal stability of the dispersion state of the CNT dispersion and further enhancing the conductivity of the molded body, the CNT dispersion of the present invention preferably contains water as the solvent. Note that the CNT dispersion of the present invention may contain one kind of organic solvent or may contain two or more kinds of organic solvents.
[0028] Here, in the CNT dispersion of the present invention, the ratio of water in the solvent is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass (i.e., the CNT dispersion of the present invention contains only water as the solvent), with the total amount of the solvent being 100% by mass. If the ratio of water in the solvent in the CNT dispersion is at least the above lower limit, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0029] <Dispersant> The CNT dispersion of the present invention contains a dispersant having a weight average molecular weight of less than 40,000. Examples of such dispersants include water-soluble polymers such as cellulose-based polymers, polycarboxylic acids, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl methyl ether, poly-N-vinylacetamide, polyacrylamide, and polyimide. In the present invention, when a polymer is "water-soluble", it means that when 0.5 g (in terms of solid content) of the polymer is dissolved in 100 g of water at a temperature of 25 °C, the amount of insoluble matter is less than 10.0% by mass.
[0030] Examples of cellulose-based polymers include carboxymethyl cellulose, methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, and their salts and derivatives. Examples of polycarboxylic acids include polyacrylic acid, polymethacrylic acid, alginic acid, and their salts and derivatives. Here, examples of the above salts include alkali metal salts such as sodium salts and ammonium salts. Examples of the above derivatives include esters such as alkyl esters and ethers.
[0031] The above-described dispersants may be used alone or in combination of two or more in any ratio. Among these, from the viewpoint of further improving the temporal stability of the dispersion state of the CNT dispersion and further enhancing the conductivity of the molded body, a cellulose-based polymer is preferably used as the dispersant, and carboxymethyl cellulose and its salts are more preferred.
[0032] Note that the CNT dispersion may further contain a dispersant having a weight average molecular weight of 40,000 or more. That is, as the dispersant contained in the CNT dispersion, only a dispersant having a weight average molecular weight of less than 40,000 may be used, or a dispersant having a weight average molecular weight of less than 40,000 and a dispersant having a weight average molecular weight of 40,000 or more may be used in combination.
[0033] Here, when a dispersant having a weight average molecular weight of less than 40,000 and a dispersant having a weight average molecular weight of 40,000 or more are used in combination, the proportion of the dispersant having a weight average molecular weight of less than 40,000 is preferably 30% by mass or more, more preferably 40% by mass or more, and still more preferably 50% by mass or more, with the total amount of the dispersants (i.e., the total amount of the dispersant having a weight average molecular weight of less than 40,000 and the dispersant having a weight average molecular weight of 40,000 or more) being 100% by mass. If the proportion of the dispersant having a weight average molecular weight of less than 40,000 is 30% by mass or more, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0034] <<Weight average molecular weight>> The CNT dispersion of the present invention needs to contain a dispersant having a weight average molecular weight of less than 40,000. When the weight average molecular weight of the dispersant contained in the CNT dispersion is 40,000 or more, it becomes difficult for the dispersant to penetrate into the CNT aggregates, and the temporal stability of the dispersion state of the CNT dispersion and the conductivity of the molded body decrease. Further, the viscosity of the CNT dispersion excessively increases. And the CNT dispersion preferably contains a dispersant having a weight average molecular weight of 36,000 or less, and more preferably contains a dispersant having a weight average molecular weight of 32,000 or less. If the CNT dispersion contains a dispersant having a weight average molecular weight of 36,000 or less, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced. Also, an excessive increase in the viscosity of the CNT dispersion can be suppressed. The lower limit of the weight average molecular weight of the dispersant is not particularly limited, and can be, for example, 1000 or more, and can be 5000 or more.
[0035] <<Degree of etherification>> Here, carboxymethyl cellulose, which is preferably used as a dispersant, preferably has an etherification degree of 0.5 or more, more preferably 0.6 or more, still more preferably 0.7 or more, preferably 0.9 or less, and more preferably 0.8 or less. If the etherification degree of carboxymethyl cellulose is within the above range, aggregation of CNTs in the CNT dispersion can be suppressed, and the temporal stability of the dispersion state of the CNT dispersion can be further improved.
[0036] <<Content ratio>> The content ratio of the dispersant having a weight average molecular weight of less than 40,000 in the CNT dispersion is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, still more preferably 0.2% by mass or more, preferably 10% by mass or less, more preferably 5% by mass or less, still more preferably 2% by mass or less, and particularly preferably 1% by mass or less, with respect to 100% by mass of the total amount of the CNT dispersion. If the content ratio of the dispersant having a weight average molecular weight of less than 40,000 in the CNT dispersion is within the above range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0037] The content of the dispersant having a weight average molecular weight of less than 40,000 in the CNT dispersion is preferably 100 parts by mass or more, more preferably 200 parts by mass or more, preferably 500 parts by mass or less, and more preferably 450 parts by mass or less, per 100 parts by mass of CNTs. If the amount ratio of the dispersant having a weight average molecular weight of less than 40,000 to CNTs in the CNT dispersion is within the above range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0038] <Other components> Examples of other components that the CNT dispersion may optionally contain include conductive materials other than CNTs, polymer components other than the above-described dispersants, antioxidants, resins, and the like. Note that the CNT dispersion may contain only one type of other component or may contain two or more types of other components. The proportion of other components contained in the CNT dispersion is preferably 5% by mass or less, more preferably 1% by mass or less, still more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass (that is, the CNT dispersion of the present invention does not contain other components), with the total amount of the CNT dispersion being 100% by mass.
[0039] <Viscosity at a shear rate of 1000 (1 / s)> The viscosity of the CNT dispersion of the present invention under the condition of a shear rate of 1000 (1 / s) is preferably 1.60 mPa·s or more, more preferably 1.80 mPa·s or more, still more preferably 2.00 mPa·s or more, particularly preferably 2.20 mPa·s or more, and preferably 3.50 mPa·s or less, more preferably 3.20 mPa·s or less. If the viscosity under the condition of a shear rate of 1000 (1 / s) is within the above range, the temporal stability of the dispersion state of the CNT dispersion can be further improved, and the conductivity of the molded body can be further enhanced.
[0040] <Preparation of CNT dispersion> The CNT dispersion of the present invention can be prepared, for example, by subjecting a mixture containing the above-described CNT, solvent, dispersant, and any other optional components to a dispersion treatment. The dispersion treatment is not particularly limited, and can be performed using, for example, a mixer such as a wet jet mill, bead mill, ball mill, sand mill, pigment disperser, attritor, ultrasonic disperser, homogenizer, planetary mixer, or film mixer. Among them, from the viewpoint of further improving the temporal stability of the dispersion state of the CNT dispersion and further enhancing the conductivity of the molded body, it is preferable to use a wet jet mill. Examples of the wet jet mill include "Nanovaitor (registered trademark)" (manufactured by Yoshida Kikai Kogyo Co., Ltd.), "BERYU SYSTEM PRO" (manufactured by Mikari Co., Ltd.), an ultra-high pressure wet atomization device (manufactured by Yoshida Kogyo Co., Ltd.), "Nanomizer (registered trademark)" (manufactured by Nanomizer Co., Ltd.), and "Starburst (registered trademark)" (manufactured by Sugino Machine Ltd.).
[0041] Here, examples of the nozzles provided in the wet jet mill include a straight nozzle, a cross nozzle, etc. The straight nozzle has an I-shaped nozzle cross-section and relatively low processing energy. On the other hand, the cross nozzle has an X-shaped nozzle cross-section and higher processing energy than the straight nozzle. From the perspective of further improving the temporal stability of the dispersion state of the CNT dispersion liquid while further enhancing the conductivity of the molded body, it is preferable to use a straight nozzle as the nozzle provided in the wet jet mill.
[0042] Here, the pressure applied in the dispersion treatment of the mixed liquid by the wet jet mill is preferably 25 MPa or more, preferably 50 MPa or less, and more preferably 30 MPa or less. If the pressure applied to the mixed liquid is 25 MPa or more, the temporal stability of the dispersion state of the CNT dispersion liquid can be further improved, and the conductivity of the obtained molded body can be further enhanced. Also, if the pressure applied to the mixed liquid is 50 MPa or less, the conductivity of the obtained molded body can be further enhanced by suppressing the cutting of CNTs by the dispersion treatment.
[0043] Also, the number of passes of the dispersion treatment by the wet jet mill is preferably 20 or more, more preferably 45 or more, and preferably 50 or less. If the number of passes of the dispersion treatment by the wet jet mill is 20 or more, the temporal stability of the dispersion state of the CNT dispersion liquid can be further improved, and the conductivity of the obtained molded body can be further enhanced. Also, if the number of passes of the dispersion treatment by the wet jet mill is 50 or less, the conductivity of the obtained molded body can be further enhanced by suppressing the cutting of CNTs by the dispersion treatment.
Examples
[0044] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples. In the following description, “%” and “parts” representing amounts are based on mass unless otherwise specified. Then, in the examples and comparative examples, the average length, average diameter, average aspect ratio of the CNT bundles, the number of CNTs with a diameter exceeding 30.0 nm, the G / D ratio of the CNTs, the weight average molecular weight of the dispersant, the viscosity at a shear rate of 1000 (1 / s), the particle size change rate and the viscosity change rate, and the volume conductivity of the carbon film (molded body) were evaluated by the following methods.
[0045] <Average length, average diameter, average aspect ratio> The CNT dispersions prepared in the examples and comparative examples were diluted with pure water so that the concentration of CNTs became 25 ppm by mass. After dropping one drop of the obtained diluted solution onto a wafer with a dropper, the wafer was placed on a hot plate heated to 90 °C and baked for 1 minute. The obtained CNT-coated wafer was observed using a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, product name "SU8200") under the conditions of a working distance of 3 mm, an acceleration voltage of 1.0 kV, and a magnification of 10,000 times, and a plurality of SEM images containing 10 or more CNT bundles in the field of view were acquired. For 100 CNT bundles arbitrarily extracted from the acquired SEM images, the diameter (outer diameter) and length of the bundles were measured. Then, the arithmetic mean value of the diameters (outer diameters) of the 100 measured CNT bundles was defined as the average diameter (nm) of the CNT bundles in the CNT dispersion. Also, the arithmetic mean value of the lengths of the 100 measured CNT bundles was defined as the average length (μm) of the CNT bundles in the CNT dispersion. The average aspect ratio was calculated by dividing the average length (nm) by the average diameter (nm). <Number of CNT bundles with a diameter exceeding 30.0 nm> As described above, the diameters (outer diameters) of 100 CNT bundles were measured, and the number of those with a diameter (outer diameter) exceeding 30.0 nm was determined. <G / D ratio> Using a microscopic laser Raman spectrophotometer (manufactured by Thermo Fisher Scientific, product name "Nicolet Almega XR"), the Raman spectra of the CNTs used in the examples and comparative examples were measured. Then, for the obtained Raman spectra, the intensity of the G-band peak observed in the vicinity of 1590 cm -1 and the intensity of the D-band peak observed in the vicinity of 1340 cm -1 The intensity of the D-band peak observed in the vicinity was determined, and the G / D ratio was calculated. <Weight-average molecular weight> The weight-average molecular weight (Mw) of the dispersant was measured using gel permeation chromatography with an aqueous solution having a dispersant concentration of 1%. Specifically, a gel permeation chromatograph (manufactured by Tosoh Corporation, product name "HLC-8220") was used, and water was used as the developing solvent to determine the weight-average molecular weight (Mw) of the dispersant as a value in terms of standard polystyrene. <Viscosity at a shear rate of 1000 (1 / s)> The viscosity (mPa·s) of the CNT dispersion was measured under the conditions of a shear rate of 1000 (1 / s), a CNT concentration of 0.1%, and a temperature of 20°C. The CNT dispersion immediately after preparation was adjusted to a CNT concentration of 0.1% by adding or removing water as necessary, and the resulting sample was used as the measurement sample. For this measurement sample, a rheometer (manufactured by Anton Paar GmbH, product name "MCR-102") was used as the measuring device, and a cone plate was used as the measuring jig. The range of shear rate from 100 to 9000 (1 / s) was measured at 20°C, and the viscosity (mPa·s) at a shear rate of 1000 (1 / s) was determined. <Temporal stability of the dispersion state> If both the "particle size change rate" and the "viscosity change rate" shown below are evaluated as A or B, it means that the CNT dispersion has excellent temporal stability of the dispersion state. [Particle size change rate] For the CNT dispersions obtained in the examples and comparative examples, the value of the average particle size (D50) immediately after preparation and the value of the average particle size (D50) 10 days after preparation were measured, respectively. The average particle size (D50) was measured with a laser diffraction / scattering particle size distribution measuring device (manufactured by HORIBA, Ltd., product name "Partica LA-960V2") using an aqueous dispersion diluted with water so that the CNT concentration was 0.01%. In the obtained particle size distribution (volume basis), the particle size at which the cumulative volume calculated from the small-diameter side was 50% was determined as the average particle size (μm). The measurement conditions were as follows. ·Circulation speed: 3, ultrasonic intensity: 7, ultrasonic time: 1 minute, stirring speed: 1, stirring mode: continuous (operation conditions of circulation / ultrasound) · Ultrasonic intensity: 7, ultrasonic time: 5 seconds (operating conditions of ultrasonic during air evacuation) · Refractive index of water: 1.333 · Refractive index of carbon material: 1.92 And, let the value of the average particle diameter (D50) immediately after preparation be d 0 (μm), and let the value of the average particle diameter (D50) 10 days after preparation be d 1 (μm). The particle size change rate (%) = [(d 1 - d 0 ) / d 0 × 100 was used to calculate the particle size change rate (%), and the evaluation was carried out according to the following criteria. The smaller the value of the particle size change rate, the less likely the dispersion state of CNT is to change, that is, it means that the dispersion state has excellent temporal stability. A: Particle size change rate is less than 1% B: Particle size change rate is 1% or more and less than 15% C: Particle size change rate is 15% or more and less than 30% D: Particle size change rate is 30% or more [Viscosity change rate] Regarding the CNT dispersion liquids obtained in the examples and comparative examples, the viscosity values immediately after preparation and the viscosity values 10 days after preparation were measured respectively. Each viscosity measurement was carried out at a temperature of 20 °C using a rheometer (manufactured by Antonpaar, product name "MCR-102"). Specifically, a cone plate was used as the measurement jig, the range of shear rate from 100 to 9000 (1 / s) was measured, and the viscosity (mPa·s) at a shear rate of 1000 (1 / s) was obtained. And, let the viscosity value immediately after preparation be η 0 (mPa·s), and let the viscosity value 10 days after preparation be η 1 (mPa·s). The viscosity change rate (%) = [(η 1 - η 0 ) / η 0 × 100 was used to calculate the viscosity change rate (%), and the evaluation was carried out according to the following criteria. The smaller the value of the viscosity change rate, the less likely the CNT dispersion liquid is to thicken over time, that is, it means that the dispersion state has excellent temporal stability. A: Viscosity change rate is less than 10% B: Viscosity change rate is 10% or more and less than 15% C: Viscosity change rate is 15% or more and 20% or less D: Viscosity change rate exceeds 20% <Volume conductivity> The volume conductivity (S / cm) of the carbon films (formed bodies) prepared in the examples and comparative examples was measured in accordance with JIS K 7194 using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., product name "Roresta-GX"), and evaluated according to the following criteria. The higher the value of this volume conductivity, the better the conductivity of the carbon film (formed body). A: Volume conductivity value exceeds 100 S / cm B: Volume conductivity value is 50 S / cm or more and 100 S / cm or less C: Volume conductivity value is less than 50 S / cm
[0046] (Example 1) <Preparation of CNT dispersion> [Synthesis of CNT] Single-walled CNTs (hereinafter referred to as "CNT-a") were produced according to the method disclosed in Example 4 of International Publication No. 2022 / 114237. The properties of the obtained CNT-a were G / D ratio: 1.2, tapped bulk density: 0.02 g / cm 3 , CNT average length: 150 μm, BET specific surface area: 600 m 2 / g, average outer diameter: 4.0 nm, and carbon purity 99.0 mass%. [Preparation of CNT dispersion] An aqueous solution (300 mL) containing sodium carboxymethyl cellulose (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Cellogen 5A"; weight average molecular weight: 13,000; degree of etherification: 0.7 - 0.8; referred to as "CMC-a") as a dispersant in water as a solvent (concentration of sodium carboxymethyl cellulose: 0.4%) was added with 0.3 g of CNT-a as the single-layer CNT obtained above (G / D ratio: 1.2) to obtain a mixed solution (concentration of CNT: 0.1%). For this mixed solution, a wet jet mill (manufactured by Yoshida Kikai Kogyo Co., Ltd., model number "NVL-ES008A-D10", product name "Nano Veta (registered trademark)") was used to perform a dispersion treatment under the conditions of a pressure of 25 MPa and a number of passes of 30 times. Specifically, while applying back pressure, a shear force was applied to the mixed solution to disperse the CNTs, and a CNT dispersion was obtained. For the obtained CNT dispersion, the average length, average diameter, and average aspect ratio of the CNT bundles, the number of CNT bundles with a diameter exceeding 30.0 nm, as well as the particle size change rate and viscosity change rate were measured. The results are shown in Table 1. <Preparation of Carbon Film (Formed Body)> The CNT dispersion prepared above was filtered under the condition of 0.09 MPa using a vacuum filtration device equipped with a membrane filter. After the filtration was completed, isopropyl alcohol and water were each passed through the vacuum filtration device to wash the carbon film formed on the membrane filter, and then air was passed through for 15 minutes. Next, the carbon film / membrane filter was immersed in ethanol, and the carbon film was peeled off from the membrane filter to obtain a carbon film as a formed body. The obtained carbon film was the same size as the membrane filter, had excellent film-forming properties, and maintained its film state even after being peeled off from the filter, and also had excellent self-supporting properties. The volume conductivity of this carbon film was measured. The results are shown in Table 1.
[0047] (Example 6) When preparing the CNT dispersion, instead of CNT-a as the single-walled CNT, CNT-b (manufactured by Nippon Zeon Co., Ltd., product name "ZEONANO (registered trademark) SG101"; G / D ratio: 5.0) was used, and the pressure and number of passes of the dispersion treatment by the wet jet mill were changed as shown in Table 1. Otherwise, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, the evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.
[0048] (Example 11) When preparing the CNT dispersion, instead of CMC-a as the dispersant, sodium carboxymethyl cellulose (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name "Cellogen 7A"; weight average molecular weight: 30,000; degree of etherification: 0.7 to 0.8; referred to as "CMC-b") was used, and the pressure and number of passes of the dispersion treatment by the wet jet mill were changed as shown in Table 1. Otherwise, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, the evaluation was carried out in the same manner as in Example 1. The results are shown in Table 1.
[0049] (Comparative Example 5) When preparing the CNT dispersion, instead of CMC-a as the dispersant, sodium carboxymethyl cellulose (manufactured by Nippon Paper Industries Co., Ltd., product name "Sunrose MAC (registered trademark) 01LC"; weight average molecular weight: 55,800; degree of etherification: 0.7 to 0.8; referred to as "CMC-c") was used, and the pressure and number of passes of the dispersion treatment by the wet jet mill were changed as shown in Table 3. Otherwise, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, the evaluation was carried out in the same manner as in Example 1. The results are shown in Table 3.
[0050] (Examples 2 to 5, 7 to 10 and 12 to 21, Comparative Examples 1 to 4 and 6 to 7) When preparing the CNT dispersion, the types of CNT and the dispersant, and the pressure and number of passes of the dispersion treatment by the wet jet mill were changed as shown in Tables 1 to 3. Otherwise, the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1. Then, the evaluation was carried out in the same manner as in Example 1. The results are shown in Tables 1 to 3.
[0051] (Example 22) When preparing the CNT dispersion, instead of CMC-a as the dispersant, a mixture of CMC-a and CMC-c at a ratio of 1:1 (mass ratio) was used, and the preparation of the CNT dispersion and the production of the carbon film were carried out in the same manner as in Example 1 except that the pressure and the number of passes of the dispersion treatment by the wet jet mill were changed as shown in Table 2. Then, the evaluation was carried out in the same manner as in Example 1. The results are shown in Table 2.
[0052] In Tables 1 to 3 shown below, "CNT" represents single-walled carbon nanotubes, "CMC" represents sodium carboxymethyl cellulose, "Mw" represents the weight average molecular weight, "Number of CNT bundles with a diameter exceeding 30 nm" represents the number of CNT bundles with a diameter exceeding 30.0 nm among 100 CNT bundles. Also, "average length of CNT bundles" is expressed as a value rounded to the third decimal place, "average diameter of CNT bundles" is expressed as a value rounded to the second decimal place, and "average aspect ratio of CNT bundles" is expressed as a value rounded to the first decimal place.
[0053] [Table 1]
[0054] [Table 2]
[0055] [Table 3]
[0056] From Tables 1 to 3, it can be seen that in Examples 1 to 22 using a CNT dispersion liquid containing single-walled CNTs, a solvent, and a dispersant having a weight-average molecular weight of less than a predetermined value, the average length of the CNT bundles is not less than a predetermined value, the average diameter of the CNT bundles is less than a predetermined value, and the number of CNT bundles having a diameter exceeding 30.0 nm is not more than a predetermined value, a CNT dispersion liquid excellent in the temporal stability of the dispersion state and a carbon film excellent in conductivity can be produced. On the other hand, in Comparative Examples 1 to 7 in which at least one of the weight-average molecular weight of the dispersant, the average length of the CNT bundles, the average diameter of the CNT bundles, and the number of CNT bundles having a diameter exceeding 30.0 nm does not satisfy the predetermined conditions, it can be seen that either or both of the temporal stability of the dispersion state of the CNT dispersion liquid and the conductivity of the carbon film are degraded as compared with Examples 1 to 22.
Industrial Applicability
[0057] According to the present invention, it is possible to provide a carbon nanotube dispersion liquid that is excellent in the temporal stability of the dispersion state and capable of forming a molded article excellent in conductivity.< / cnt>
Claims
1. A carbon nanotube dispersion liquid containing a plurality of carbon nanotubes, a solvent, and a dispersant having a weight average molecular weight of less than 40,000, wherein the plurality of carbon nanotubes include single-walled carbon nanotubes, at least a part of the plurality of carbon nanotubes forms a carbon nanotube bundle, the average length of the carbon nanotube bundle is 1.50 μm or more, the average diameter of the carbon nanotube bundle is less than 14.7 nm, in 100 carbon nanotube bundles, the number of those with a diameter exceeding 30.0 nm is 10 or less, the carbon nanotube dispersion liquid.
2. The carbon nanotube dispersion liquid according to Claim 1, wherein the G / D ratio of the carbon nanotubes is 0.5 or more and 120 or less.
3. The carbon nanotube dispersion liquid according to Claim 1, wherein the average aspect ratio of the carbon nanotube bundle is 110 or more.
4. The carbon nanotube dispersion liquid according to any one of Claims 1 to 3, wherein the dispersant is carboxymethyl cellulose or a salt thereof.
5. The carbon nanotube dispersion liquid according to Claim 4, wherein the degree of etherification of the carboxymethyl cellulose is 0.5 or more and 0.9 or less.
Citation Information
Patent Citations
Carbon nanotube dispersion liquid for non-aqueous electrolyte secondary battery, resin composition using the same, mixture slurry, electrode film, and non-aqueous electrolyte secondary battery
JP2021072279A
Carbon nanotube dispersion and usage therefor
WO2020004095A1